2023
DOI: 10.3390/s23135782
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Prostheses: Engineering and Clinical Perspectives for Vision Restoration

Abstract: A retinal prosthesis, also known as a bionic eye, is a device that can be implanted to partially restore vision in patients with retinal diseases that have resulted in the loss of photoreceptors (e.g., age-related macular degeneration and retinitis pigmentosa). Recently, there have been major breakthroughs in retinal prosthesis technology, with the creation of numerous types of implants, including epiretinal, subretinal, and suprachoroidal sensors. These devices can stimulate the remaining cells in the retina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 147 publications
0
17
0
Order By: Relevance
“…Gene augmentation, or gene replacement, is an approach that replaces a dysfunctional gene with a functional copy to promote the production of functional proteins [9,12]. This approach is simple and directly utilizes a viral or non-viral vector to deliver the functional gene.…”
Section: Gene Augmentationmentioning
confidence: 99%
“…Gene augmentation, or gene replacement, is an approach that replaces a dysfunctional gene with a functional copy to promote the production of functional proteins [9,12]. This approach is simple and directly utilizes a viral or non-viral vector to deliver the functional gene.…”
Section: Gene Augmentationmentioning
confidence: 99%
“…A retinal prosthesis is an implantable device that may improve vision in individuals with profound vision loss due to photoreceptor loss by stimulating electrical activity from the damaged outer retina to more intact inner layers. These surgically placed devices have been studied in the epiretinal, subretinal, and suprachoroidal spaces 50 . In 2014, the first human trial involving a suprachoroidal retinal prosthesis suggested an easier surgical approach with fewer intraocular adverse events based on its three study participants 51 .…”
Section: Suprachoroidal Retinal Prosthesismentioning
confidence: 99%
“…The retina, originating from the optic cup’s inner and outer layers, is a multilayered structure integral to visual processing ( Figure 5 ). In a proximal to distal arrangement, it consists of 10 specialized layers [ 31 ]:…”
Section: Ocular Anatomy and Physiologymentioning
confidence: 99%